Children of the future preschool educator development of knowledge on physiology –As a pedagogical problem - Tadjibaeva Gavharoy Ismailovna (Zien Journals, 2022)
In the article, taking into account the specific features of the field of preschool education, the development of the future preschool teacher's knowledge of children's physiology, initially consists in explaining the social essence of his profession.
Keywords: Preschool education; physiology; hygiene; first educator